2009
DOI: 10.4319/lo.2009.54.5.1501
|View full text |Cite
|
Sign up to set email alerts
|

Microbial oceanography of the dark ocean's pelagic realm

Abstract: The pelagic realm of the dark ocean represents a key site for remineralization of organic matter and long-term carbon storage and burial in the biosphere. It contains the largest pool of microbes in aquatic systems, harboring nearly 75% and 50% of the prokaryotic biomass and production, respectively, of the global ocean. Genomic approaches continue to uncover the enormous and dynamic genetic variability at phylogenetic and functional levels. Deep-sea prokaryotes have comparable or even higher cell-specific ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

42
434
7
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 446 publications
(485 citation statements)
references
References 254 publications
(377 reference statements)
42
434
7
2
Order By: Relevance
“…Taken together, the notion emerges that deep-water prokaryotes are predominantly opportunists, presumably well adapted to a particle-attached life mode (Lauro and Bartlett, 2008;Aristegui et al, 2009), which might explain the need for a larger genome size. Hence, the larger genome of prokaryotes in the deep waters corresponds to the higher fraction of high fluorescence viruses found in the abyssopelagic compared with the bathypelagic waters (Supplementary Figures S3b, Figure S4b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the notion emerges that deep-water prokaryotes are predominantly opportunists, presumably well adapted to a particle-attached life mode (Lauro and Bartlett, 2008;Aristegui et al, 2009), which might explain the need for a larger genome size. Hence, the larger genome of prokaryotes in the deep waters corresponds to the higher fraction of high fluorescence viruses found in the abyssopelagic compared with the bathypelagic waters (Supplementary Figures S3b, Figure S4b).…”
Section: Discussionmentioning
confidence: 99%
“…However, the lack of a specific trend with depth in lysogenic VP along with its considerable variability points to substantial patchiness in the interaction between viruses and prokaryotes in the bathy-and abyssopelagic realms. Recently, Aristegui et al (2009) reviewed deepwater prokaryotic abundance and activity and viral abundance and concluded that the variability in these parameters is as high in the deep ocean as in surface waters despite their decrease in average abundance by orders of magnitude over this depth range. In our study, heterotrophic prokaryotic activity decreased by three orders of magnitude from the epi-to the abyssopelagic layer and was generally similar to that reported for the deep waters of the southern region of the North Atlantic (Reinthaler et al, 2006).…”
Section: Viral and Heterotrophic Prokaryotic Productionmentioning
confidence: 99%
“…Because V a,4 exhibits a high m E,1 and considering the range of the other parameters within the equation, especially m, j M has to be high. Such a result draws the interest because it appears coherent when compared with some data acquired at a much larger scale [37]. It leads us to define V a,4 as the class fulfilling the b-condition, and rewrite V a,4 ¼ V b .…”
Section: Building the Treementioning
confidence: 99%
“…Although several studies have shown that viral particles are abundant in bathy pelagic waters [10][11][12] , the source and fate of these deep sea viruses are unclear. Compared with surface waters, the decay rate of virioplankton in the deep sea is decreased by two to three orders of magnitude, which might contribute -at least partially -to the high number of viruses in the deep sea 10,13 .…”
mentioning
confidence: 99%
“…Compared with surface waters, the decay rate of virioplankton in the deep sea is decreased by two to three orders of magnitude, which might contribute -at least partially -to the high number of viruses in the deep sea 10,13 . Very limited measurements of viral production and the decay rate have suggested allochthonous inputs of viruses, on sedimentation particles, to the deep sea [9][10][11][12][13] . Nevertheless, as an organic form, the elemental constituents of viruses should be more important in the deep sea than in the upper ocean as most DOM in the deep sea is refractory 14 .…”
mentioning
confidence: 99%